Medical Migration : What Can We Learn from the UK's Perspective? - Rutten, Martine (World Bank, Washington, DC, 2012)
This paper seeks to determine the macro-economic impacts of migration of skilled medical personnel from a receiving country's perspective. The resource allocation issues are explored in theory, by developing an extension of the Rybczynski theorem in a low-dimension Heckscher-Ohlin framework, and empirically, by developing a static computable general equilibrium model for the United Kingdom with an extended health sector component. Using simple diagrams, an expansion of the health sector by recruiting immigrant skilled workers in certain cases is shown to compare favorably to the (short-term) long-term alternative of using domestic (unskilled) workers. From a formal analysis, changes in non-health outputs are shown to depend on factor-bias and scale effects. The net effects generally are indeterminate. The main finding from the applied model is that importing foreign doctors and nurses into the United Kingdom yields higher overall welfare gains than a generic increase in the National Health Service budget. Welfare gains rise in case of wage protection.